Conceptual framwork of screw pine leaves biocomposite for furniture component - Zainol, Izyan Syamimi; Abd Rahman, Khairul Aidil Azlin; Ramli, Saiful Hasley (2016)
The purpose of this paper is to provide a review of the literature and framework study of the screw pine leaves bio-composites for furniture components. In Malaysia, the material is commonly used in making the handicraft product, this study is executing the screw pine leaves to be proposed as one of the bio-composite material. The intention of producing the screw pine leaves bio-composite material is to apply it on the furniture component that is a high value added product, which could create a niche market on the material. The experimental method is used in the study. As the preliminary study, the screw pine leaves need to be recognized. The specific data of screw pine leaves bio-composite are collected from referring ASTM D3379 -75 Standard for tensile strength, while ASTM D256-06 Standard for impact testing. Then, the bio-composite screw pine leaves that reinforced with a biodegradable adhesive is applied to a furniture component. The study also validates on the market and specific data testing as tensile and impact test. The records are sorted into sections of material properties of screw pine leaves and validate data on the material properties of screw pine leaves bio-composite, and material application of the design. This study is expected to record all the specific data for future used, other than proposing a new furniture component design based on the screw pine leaves bio-composite material.